2016 SIIL Annual Meeting - Unlocking the production potential of polder communities in coastal Bangladesh - Jagadish, Krishna S.V. (2016)
Dr. Krishna Jagadish, PI of the Bangladesh subaward funded by the Feed the Future Innovation Lab for Collaborative Research on Sustainable Intensification (SIIL), presents his project to the SIIL community. Filmed in January 2016.